(untitled) (Stylos, 2019)
In this paper, we will analyze the love stories in Ovid’s Metamorphoses in which the god Apollo and a mortal have the leading role – Daphne (Met. 1.452-567), Coronis (2.542-632), Cyparissus (10.86-142), Hyacinth (10.162-219), Chione (11.266-345), and the Cumaean Sibyl (14.102-157). The concepts of “repetition”, “narrative continuity” and “closure”, formulated by S. Wheeler in Narrative Dynamics in Ovid’s Metamorphoses (2000), will be used as theoretical framework to examine the narrative patterns presented in these passages. We will observe in which way Daphne’s episode, primus amor Phoebi, establishes a series of features that shape the reader’s expectations regarding the subsequent love stories. The story about the Cumaean Sibyl, on the other hand, closes the sequence of Apollo’s love stories and, at the same time, announces the ending of the poem.